Bone Marrow Mesenchymal Stem Cells-derived Exosomes Promote Survival of Random Flaps in Rats through Nrf2-mediated Antioxidative Stress - Zhu, Lin; Niu, Qifang; Li, Delong; Li, Mozi; Guo, Wenwen; Han, Zhengxue; Yang, Yang (Journal of Reconstructive Microsurgery, 2024)
Background Random flaps are the most used defect repair method for head and neck tumors and trauma plastic surgery. The distal part of the flap often undergoes oxidative stress (OS), ultimately leading to flap necrosis. Stem cells' exosomes exhibit potential effects related to anti-inflammatory, regenerative, and antioxidant properties. Nuclear factor erythroid-2-related factor 2 (Nrf2) is an important factor in regulating oxidative balance. Exosomes have been reported to monitor its transcription to alleviate OS. This study examined the impacts and underlying mechanisms of antioxidant actions of exosomes derived from bone marrow mesenchymal stem cells (BMSCs-Exo) on random flaps.Methods BMSCs-Exo were injected into the tail veins of rats on days 0, 1, and 2 after surgery of random flaps. The rats were euthanized on day 3 to calculate the survival rate. Immunohistochemical staining, western blotting, dihydroethidium probe, superoxide dismutase, and malondialdehyde assay kits were used to detect the OS level. Human umbilical vein endothelial cells were cocultured with BMSCs-Exo and ML385 (an inhibitor of Nrf2) in vitro.Results BMSCs-Exo may significantly improve the survival rate of the random flaps by reducing apoptosis, inflammation, and OS while increasing angiogenesis. Besides, BMSCs-Exo can also increase mitochondrial membrane potential and reduce reactive oxygen species levels in vitro. These therapeutic effects might stem from the activation of the Kelch-like enyol-CoA hydratase (ECH)-associated protein 1 (Keap1)/Nrf2 signaling pathway.Conclusion BMSCs-Exo improved the tissue antioxidant capacity by regulating the Keap1/Nrf2 signaling pathway. BMSCs-Exo may be a new strategy to solve the problem of random flap necrosis.
Keywords: random flaps; bone marrow mesenchymal stem cells-derived exosomes; oxidative stress